Evaluation of Bi-Layer Silk Fibroin Grafts for Tubular Ureteroplasty in a Porcine Defect Model - Gundogdu, Gokhan; Okhunov, Zhamshid; Cristofaro, Vivian; Starek, Stephanie; Veneri, Faith; Orabi, Hazem; Jiang, Pengbo; Sullivan, Maryrose P.; Mauney, Joshua R. (Frontiers in Bioengineering and Biotechnology, 2021)
Ureteral reconstruction with autologous tissue grafts is often limited by tissue availability and donor site morbidity. This study investigates the performance of acellular, bi-layer silk fibroin (BLSF) scaffolds in a porcine model of ureteroplasty. Tubular ureteroplasty with BLSF grafts in combination with transient stenting for 2 months was performed in adult female, Yucatan, mini-swine (N=5). Animals were maintained for 3 months post-op with monthly imaging of neoconduits using ultrasonography and retrograde ureteropyelography. End-point analyses of ureteral neotissues and unoperated controls included histological, immunohistochemical (IHC), histomorphometric evaluations as well as ex vivo functional assessments of contraction/relaxation. All animals survived until scheduled euthanasia and displayed mild hydronephrosis (Grades 1-2) in reconstructed collecting systems during the 2 month stenting period with one animal presenting with a persistent subcutaneous fistula at 2 weeks post-op. By 3 months of scaffold implantation, unstented neoconduits led to severe hydronephrosis (Grade 4) and stricture formation in the interior of graft sites in 80% of swine. Bulk scaffold extrusion into the distal ureter was also apparent in 60% of swine contributing to ureteral obstruction. However, histological and IHC analyses revealed the formation of innervated, vascularized neotissues with α-smooth muscle actin+ and SM22α+ smooth muscle bundles as well as uroplakin 3A+ and pan-cytokeratin+ urothelium. Ex vivo contractility and relaxation responses of neotissues were similar to unoperated control segments. BLSF biomaterials represent emerging platforms for tubular ureteroplasty, however further optimization is needed to improve in vivo degradation kinetics and mitigate stricture formation.